S109 Five-Repetition Sit-To-Stand Test: Reliability, Validity and Response to Pulmonary Rehabilitation in COPD. (19th November 2012) - Jones, SE; Kon, SSC; Canavan, JL; Clark, AL; Patel, MS; Dilaver, D; Peasey, M; Ng, MGS; Polkey, MI; Man, WD-C
Abstract : Background: Validated field exercise tests, such as the six minute walk test and incremental/endurance shuttle walks, require space and may be time-consuming as repeat walks are needed due to learning effect. Hence they are rarely used outside the research or pulmonary rehabilitation (PR) setting. The five-repetition Sit to Stand test (STS) is a simple test that is feasible in most settings. It measures the quickest time taken to stand and sit five times from a chair, with arms folded. We hypothesized that the STS would be reliable, correlate with the incremental shuttle walk (ISW), and be responsive to PR. Methods: The STS was measured in 80 COPD patients on two occasions 24–48 hours apart. Test-retest reliability was calculated using ICCs. STS and ISW were measured in a convenience sample of 396 COPD patients (Mean (SD) age 69 (10); FEV1%predicted 47 (20); ISW 202 (141)) recruited from hospital outpatient clinics. Spearman rank correlation was used to evaluate the relationship between STS and ISW. The STS was measured before and after an 8-week outpatient PR programme in 168 COPD patients. Paired t-tests were used to compare pre- and post-PR outcomes. Results: The STS demonstrated excellent test-retest reliability with an ICC value of 0.99 with no learning effect. A significant correlation was seen between STS and ISW (rho = –0.68; p<0.001). The STS improved significantly following PR (Pre: 20.91 (16.23) versus Post: 17.87 (14.93) seconds; 95% confidence interval –1.5 to –4.6 seconds; p<0.001). Conclusions: The STS is reliable, correlates with the incremental shuttle walk, and is responsive to PR in patients with COPD. The STS is a practical functional outcome measure suitable for use in most healthcare settings.